Enforceability of Restrictive Covenants in Employment Contracts: Comparing India and Indonesia (Law Research Review Quarterly, 2022)
In contemporary times, one of the fundamentals that bind and guide any professional relationship is a contract and throughout the negotiations, the parties to it try to assert their interests for ensuring gains. In this process, quite often, several clauses are inserted for ensuring greater exploitation without greater investments and this is witnessed quite often in India and Indonesia, especially in employer-employee contracts. Referred to as restrictive covenants, the Indian Courts have often interpreted the Indian Contract Act 1872 in a progressive fashion, duly preventing the employee from being reduced to a bonded labourer, on numerous occasions. But this does not mean that in all the situations, such covenants are impermissible—the extent to which an employer can restrict the employee for maintaining confidentiality andprotecting trade secrets among other things is what is largely determined by the Courts. Furthermore, in Indonesian context, the contract law stipulated not only in Article 1313 Indonesian Civil Code, but also in various acts such as Indonesian Emplopyment Act 2003 and Government Regulation No. 35 of 2021 concerning Work Agreements for Certain Time, Outsourcing, Working Time and Rest Time, and Termination of Employment. Discussing and comparing the stance of the Indian Judiciary and Indonesian contract system on such restrictive covenants, the Authors, through the medium of this paper seek to shed light on the extent to which they are enforceable and, in the circumstances, where they are valid. In a nutshell, the Authors seek to warn the employers to refrain from engaging in such practices which are likely to harm the principles of humanism enshrined in the Constitution and alert the employee of the scope of their duties towards the employer.